Conquering Oppression through Cosmopolitanism: Islam, Race, and Racism in Writings of Edward Wilmot Blyden and Cheikh Ahmadou Bamba - Mbaye, Babacar (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2024)
Abstract: This essay analyzes the Sufi religious thoughts of Cheikh Ahmadou Bamba, the founder of the Murid Islamic brotherhood of Senegal, as reflections of the cosmopolitan openness to the “other” and the rest of the world that the Pan-African scholar, Edward Wilmot Blyden, celebrates in his book, entitled Christianity, Islam and the Negro Race (1887). Blyden admired, in late nineteenth-century West African Islamic traditions, cosmopolitanism, and rejections of violence that one also finds in Bamba’s book, Mawahibul Quddus. Bamba’s text was produced in the late nineteenth century and was translated into English in 2003 as God’s Sacred Identity.Using Blyden’s book as an early exploration of the West African cosmopolitan tradition of resistance and celebration of rationality that mesmerized him, this essay explores how similar ideas were noticeable in Bamba’s Sufism. In his theology, Bamba also examines how reason and cosmopolitanism can dismantle racial and other forms of intolerance and domination.Abstrak: Esai ini menganalisis pemikiran religius Sufi dari Cheikh Ahmadou Bamba, pendiri  Murid Islamic brotherhoodof Senegal, sebagai refleksi keterbukaan kosmopolitan terhadap "yang lain" dan dunia, yang dirayakan oleh cendekiawan Pan-Afrika, Edward Wilmot Blyden dalam bukunya yang berjudul Christianity, Islam and the Negro Race (1887). Blyden mengagumi tradisi Islam Afrika Barat pada akhir abad ke-19 yang menunjukkan kosmopolitanisme dan penolakan terhadap kekerasan, yang juga ditemukan dalam buku Bamba, Mawahibul Quddus. Teks Bamba ini ditulis pada akhir abad ke-19 dan diterjemahkan ke dalam bahasa Inggris pada tahun 2003 dengan judul God’s Sacred Identity. Dengan menggunakan buku Blyden sebagai eksplorasi awal tradisi kosmopolitanisme Afrika Barat yang menawan baginya, esai ini mengeksplorasi bagaimana ide serupa terlihat dalam sufisme Bamba. Dalam teologinya, Bamba juga mengkaji bagaimana akal dan kosmopolitanisme dapat membongkar intoleransi rasial dan bentuk dominasi lainnya.